Virtual screening, molecular docking and identification of umami peptides derived from Oncorhynchus mykiss - Wenzhu Zhao; Lijun Su; Shitong Huo; Zhipeng Yu; Jianrong Li; Jingbo Liu (Food Science and Human Wellness)
Oncorhynchus mykiss is delicious and contains abundant flavor substances. However, few studies focused on umami peptides of O. mykiss. In the current work, umami peptides derived from O. mykiss were identified using virtual screening, molecular docking, and electronic tongue analysis. First, the O. mykiss protein was hydrolyzed using the PeptideCutter online enzymolysis program. Subsequently, water-soluble and toxicity screening were performed by Innovagen and ToxinPred software, respectively. The potential peptides were docked with umami receptor T1R1/T1R3. Furthermore, taste properties of potential peptides were validated by electronic tongue. Docking results suggested that the three tetrapeptide EANK, EEAK, and EMQK could enter the binding pocket in the T1R1 cavity, wherein Arg151, Asp147, Gln52, and Arg277 may play key roles in the production of umami taste. Electronic tongue results showed that the umami value of EANK, EEAK, and EMQK were stronger than monosodium glutamate. This work provides a new insight for the screening of umami peptides in O. mykiss.